1964
DOI: 10.1037/h0041485
|View full text |Cite
|
Sign up to set email alerts
|

An empirical validation of the concept of coherence.

Abstract: A set of 100 plane figures varying from 80 to 80.9 mm. in height and width were presented to 10 Os. Each 0 was asked to assign the stimuli to 1 of 4 categories: large rectangle, small rectangle, large square, small square. The probability of a correct judgment was at the chance level. A multivariate analysis of variance showed that there was a significant "form effect," and size effect but no interaction. The implications were related to the concept of coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1965
1965
1972
1972

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These results confirm and extend results from previous studies in this laboratory. In the first study Rodwan (1964) showed that when 5"s were required to assign plane figures into one of four categories.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm and extend results from previous studies in this laboratory. In the first study Rodwan (1964) showed that when 5"s were required to assign plane figures into one of four categories.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study Rodwan (1964) showed that Ss produced larger F ratios when discriminating squares from rectangles than they did when discriminating large from small twodimension figures. The stimuli were 100 different plane figures.…”
mentioning
confidence: 89%
“…(For more detail on the LDF see Rodwan & Hake, 1964. ) The derived LDF was used to give a numerical value to each form used in this experiment; furthermore, the theoretical "form" axis derived from judgments of "square" vs. "rectangle" by Rodwan (1964) was also used to give another numerical value to each form. These two values were then correlated for each 5.…”
mentioning
confidence: 99%
“…, and Rodwan and Hake (1964), and Rodwan (1964) have offered evidence for the argument that perception is a coherence-detecting system. Coherence detection is a technique used by communication receivers which enables them to separate signals from noise whenever a correlation can be established between some components of a noisy signal and a standard of comparison.…”
mentioning
confidence: 99%